2008
DOI: 10.1186/1757-1626-1-281
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of co-existence of 4th and 5thshort metacarpal bones, sesamoid ossicles and exostoses of ulna and radius in the same hand: a case report

Abstract: Introduction: The anatomical variations of bones in the hand are common. The existence of exostosis and shortening of metacarpal bones has been described in the literature as part of the hereditary multiple exostosis syndrome but no case has been reported with the co-existence of sesamoid ossicles in the same patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Over 40% of the patients with MHE had at least 1 BMC or BMT, which is higher than the previously reported incidences. 7 8 9 10 11) This discrepancy can be attributable to differences in the timing of assessment or assessment criteria between reports. In the current study, plain radiographs obtained from patients over 10 years of age were used to improve objectivity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Over 40% of the patients with MHE had at least 1 BMC or BMT, which is higher than the previously reported incidences. 7 8 9 10 11) This discrepancy can be attributable to differences in the timing of assessment or assessment criteria between reports. In the current study, plain radiographs obtained from patients over 10 years of age were used to improve objectivity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various authors have reported this metacarpal finding to be associated with a number of conditions namely Turner Syndrome, Albright's hereditary osteodystrophy, pseudohypoparathyroidism, pseudopseudohypoparathyroidism, basal cell nevus syndrome, sickle cell disease, hereditary multiple exostosis, and homocystinuria. 1,2,[4][5][6] An incidence of 4 to 10% of metacarpal sign has been reported in large series. 1,2 Here, we are reporting three cases of metacarpal sign and its variants.…”
Section: Introductionmentioning
confidence: 99%
“…Estos huesos también se presentan ocasionalmente a nivel de la articulación de la muñeca, por delante de los huesos piramidal y hamato (Tzaveas et al, 2008) Basado en lo anterior y con el propósito de determinar la presencia y su localización respecto a las diferentes articulaciones metacarpo-falángicas (AMF), estudiamos estos huesos en dos grupos de personas, uno que provenía de la región central de Chile y el otro de la región sur de Brasil.…”
Section: Introductionunclassified